Mild Neonatal Brain Hypoxia-Ischemia in Very Immature Rats Causes Long-Term Behavioral and Cerebellar Abnormalities at Adulthood - Sanches, Eduardo Farias; van de Looij, Yohan; Toulotte, Audrey; Sizonenko, Stéphane Vladimir; Lei, Hongxia (Frontiers in Physiology, 2019)
Injuries resulting from preterm birth in humans, including systemic hypoxia-ischemia (HI), converge to hinder brain cells. Following HI, forebrain structures are the most damaged, however, lesions in distant regions from the injury site are also observed. Cerebellum is becoming a target of interest. We investigated locomotion as well as the cerebellum neurochemical profile using in vivo 1H magnetic resonance spectroscopy (1H-MRS) and protein expression of neuroglial markers following early postnatal HI. At 3 days of life, pup’s right carotid artery was occluded followed by systemic hypoxia. From PND45, animals were tested for locomotion in the open field (OF), cylinder and beam balance tasks. Following behavioral analysis, the neurochemical profile in the cerebellum was assessed by 1H-MRS in a 14.1 T scanner. Right and left cerebellum were dissected and stored at -80°C. GFAP, NeuN and MBP protein expression were assessed. In the OF, HI increased locomotion. No asymmetrical forelimb use, as well as coordination deficits were observed in the motor tasks. In the 1H-MRS, metabolic differences between cerebellar hemispheres in the SHAM group, e.g. GSH and Gly were observed. However, such differences were abolished in HI rats. In addition, a global increase in Gln of HI rats was observed and was significant in the contralateral (left) cerebellum compared to the SHAM (SH) group. Furthermore, metabolic increases only occurred in [Glu], [Gly], [Glu+Gln] and [GPC+PCho] in the left cerebellar hemisphere of HI rats. There were decreased expression of MBP and NeuN but no detectable reactive astroglyosis in the contralateral hemisphere of HI rats. Taken together, the detected alterations observed in the contralateral cerebellum of HI rats may reflect a disequilibrium in the glutamate-glutamine cycle and a delay in the return of glutamine from astrocytes to neurons from hypoxic-ischemic origin, namely ipsilateral forebrain. Our data provides original in vivo evidence of long-term changes in the contralateral cerebellum following neonatal HI in very immature rats. Our in vivo observations and ex vivo analysis support the notion that systemic HI could cause cell death in a contralateral distant region from the expected injury site suggesting that long-term therapies need to be considered for this pathology.